Alice in wonderland - Carroll, Lewis, 1832-1898.; Zwerger, Lisbeth (Delhi : North-South Books, 1993)
A little girl falls down a rabbit hole and discovers a world of nonsensical and amusing characters.
"A Michael Neugebauer book."
Keywords: Fantasy